(untitled) (Journal of Population and Development, 2022)
This study aims at assessing the process of writing research proposal with its format and lay out used by different researchers and institutions. Using secondary sources of data, the study embarks the structure of the research proposal discussing with regards to the key sections of the proposal like proposal format provided by various institution, cover page, introduction, literature review, research and research question, research purpose and objectives, significance of the study, limitations and delimitations of the study, research methodology, ethical considerations, timeline, budget estimations and references employing a descriptive research design. Simple descriptive tools, content analysis and tables have been used for analysis of data. A research proposal is a detail description of a proposed study designed to explore a given problem. An excellent carved proposal has more possibility of persuading the evaluation committee on credibility, achievability, practicality and reproducibility of the research design as the evaluation committees may constitute academic colleagues, policy makers, practitioners and lay audience who potentially evaluate the research proposal. The first class research proposal includes practicality, broader linking, crystal clarity and good plan and also contains the concern literatures that support the study as well as writer’s thought explaining all about the time needed to conduct the each stage of the research.